2007
DOI: 10.1177/0091270007304780
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a Pharmacokinetic Interaction Between Entecavir and Adefovir

Abstract: This study evaluated the effect of entecavir on the pharmacokinetics of adefovir and the effect of adefovir on the pharmacokinetics of entecavir using a fixed-sequence crossover design in healthy adult subjects. Subjects received 10 mg of adefovir once daily on days 1 to 4, 1 mg of entecavir on days 5 to 14, and 1 mg of entecavir plus 10 mg of adefovir on days 15 to 24. Pharmacokinetic assessments were performed on days 4 and 24 for adefovir and on days 14 and 24 for entecavir. The geometric mean ratios (90% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The results of this study demonstrated that reducing the ETV dose in combination with ADV did not diminish the efficacy of viral suppression and did not increase the emergence of genotypic ETV‐R variants. Several previous studies had reported that a combination therapy of ETV plus ADV was well tolerated, did not showed a pharmacokinetic interaction, and produced additive antiviral effects against CHB in vitro [Delaney et al, ; Bifano et al, ]. These additive or synergistic antiviral effects attenuated the need for higher dose of ETV in combination with ADV, as shown in this study.…”
Section: Discussionsupporting
confidence: 76%
“…The results of this study demonstrated that reducing the ETV dose in combination with ADV did not diminish the efficacy of viral suppression and did not increase the emergence of genotypic ETV‐R variants. Several previous studies had reported that a combination therapy of ETV plus ADV was well tolerated, did not showed a pharmacokinetic interaction, and produced additive antiviral effects against CHB in vitro [Delaney et al, ; Bifano et al, ]. These additive or synergistic antiviral effects attenuated the need for higher dose of ETV in combination with ADV, as shown in this study.…”
Section: Discussionsupporting
confidence: 76%
“…25 Such combination treatments will likely be evaluated in patients with CHB who are currently undergoing treatment with SOC (nucleoside/nucleotide analogs; e.g., tenofovir and entecavir). These antiviral agents are typically eliminated by active renal transport utilizing the OAT system 26 and it is important to understand how the TLR7 agonist may be eliminated. In the current study, RO7011785 was eliminated by the kidneys with urinary recovery of unchanged drug of ~ 60-67% of the administered dose across all single dose levels.…”
Section: Discussionmentioning
confidence: 99%
“…ETV and ADV have some antiviral efficacy against LAM-resistant HBV with complementary resistance profiles (24,31). A study in healthy volunteers showed no evidence of a pharmacokinetic interaction between ETV and ADV, allowing both to be safely administered without the need for dose adjustment of either (3). An in vitro study showed modest synergy between these two agents (9).…”
mentioning
confidence: 99%